Risk Analysis Implications of Dose-Response Thresholds for NLRP3 Inflammasome-Mediated Diseases: Respirable Crystalline Silica and Lung Cancer as an Example. Issue 2 (2nd April 2019) - Cox, Louis Anthony (Tony)
Chronic inflammation mediates an extraordinarily wide range of diseases. Recent progress in understanding intracellular inflammasome assembly, priming, activation, cytokine signaling, and interactions with mitochondrial reactive oxygen species, lysosome disruption, cell death, and prion-like polymerization and spread of inflammasomes among cells, has potentially profound implications for dose–response modeling. This article discusses mechanisms of exposure concentration and duration thresholds for NOD-like receptor protein 3 (NLRP3)-mediated inflammatory responses and develops a simple biomathematical model of the onset of exposure-related tissue-level chronic inflammation and resulting disease risks, focusing on respirable crystalline silica (RCS) and lung cancer risk as an example. An inflammation-mediated 2-stage clonal expansion model of RCS-induced lung cancer is proposed that explains why relatively low estimated concentrations of RCS (eg, <1 mg/m 3 ) do not increase lung cancer risk and why even high occupational concentrations increase risk only modestly (typically relative risk <2). The model of chronic inflammation implies a dose–response threshold for excess cancer risk, in contrast to traditional linear-no-threshold assumptions. If this implication is correct, then concentrations of crystalline silica (or amphibole asbestos fibers, or other environmental challenges that act via the NLRP3 inflammasome) below the threshold do not cause chronic inflammation and resulting elevated risks of inflammation-mediated diseases.